Studies on genetic variability and interrelationship in bottle gourd [Lagenaria siceraria (Mol.) Standl] (International Journal of Agricultural Research, Innovation and Technology, 2018)
The genetic parameters were studied to elucidate the genetic variability, correlation and path co-efficient analysis in thirty-nine genotypes of bottle gourd [Lagenaria siceraria (Mol.) Standl] in randomized complete block design with three replications. Observations were recorded for eleven quantitative characters viz., days to first male flower open, days to first female flower open, node number of first female flower, braches plant-1, days to harvest, number of fruits plant-1, fruit weight, fruit length, fruit girth, 100 seed weight and yield ton ha-1. The analysis of variance showed highly significant differences for all the characters studied indicating considerable variability among the genotypes. The highest GCV (35.57%) and PCV (35.62%) were observed for fruit length. The differences between GCV and PCV were high for fruit number plant-1 and days to first male flower open indicating environmental influences. High heritability associates with high estimates of genetic advance in percent of mean were noted for length of fruit, yield, girth of fruit and number of fruits plant-1. It indicated presence of additive gene effect and selection for these traits would be effective. Yield were positively and significantly correlated with fruit weight, 100 seed weight, branch plant-1 and number of fruits plant-1 .Negative associations of yield were noted with days to first male and female flower open, days to harvest and length of fruit. Path analysis revealed that fruits plant-1 (0.93) and weight of fruit (0.467) had very high positive effect on fruit yield ton ha-1 .Int. J. Agril. Res. Innov. & Tech. 8 (1): 14-17, June, 2018